Quantitative trait locus mapping and candidate gene analysis for salt tolerance at bud stage in rice - Yin, Wenjing; Lu, Tianqi; Chen, Zhengai; Lu, Tao; Ye, Hanfei; Mao, Yijian; Luo, Yiting; Lu, Mei; Zhu, Xudong; Yuan, Xi; Rao, Yuchun; Wang, Yuexing (Frontiers in Plant Science, 2023)
Soil salinization has a serious influence on rice yield and quality. How to enhance salt tolerance in rice is a topical issue. In this study, 120 recombinant inbred line populations were generated through nonstop multi-generation selfing using a male indica rice variety Huazhan (Oryza sativa L. subsp. indica cv. ‘HZ’) and a female variety of Nekken2 (Oryza sativa L. subsp. japonica cv. ‘Nekken2’) as the parents. Germination under 80 mM NaCl conditions was measured and analyzed, and quantitative trait locus (QTL) mapping was completed using a genetic map. A total of 16 salt-tolerance QTL ranges were detected at bud stage in rice, which were situated on chromosomes 3, 4, 6, 8, 9, 10, 11, and 12. The maximum limit of detection was 4.69. Moreover, the qST12.3 was narrowed to a 192 kb region on chromosome 12 using map-based cloning strategy. Statistical analysis of the expression levels of these candidate genes under different NaCl concentrations by qRT-PCR revealed that qST12.3 (LOC_Os12g25200) was significantly down-regulated with increasing NaCl concentration, and the expression level of the chlorine-transporter-encoding gene LOC_Os12g25200 in HZ was significantly higher than that of Nekken2 under 0 mM NaCl. Sequencing analysis of LOC_Os12g25200 promoter region indicated that the gene expression difference between parents may be due to eight base differences in the promoter region. Through QTL mining and analysis, a plurality of candidate genes related to salt tolerance in rice was obtained, and the results showed that LOC_Os12g25200 might negatively regulate salt tolerance in rice. The results provide the basis for further screening and cultivation of salt-tolerant rice varieties and have laid the foundation for elucidating further molecular regulation mechanisms of salt tolerance in rice.